Developing diverse learners’ conceptions of information literacy through different tools and spaces - Webber, Sheila (Nordic Journal of Information Literacy in Higher Education, 2010)
The poster will portray three activities that the presenter has used to stimulate students in the Department of Information Studies to develop their ideas about information literacy. Each of the activities encourages learners to construct their own personal understanding of information literacy by considering various conceptions and perspectives (rather than trying to impose a “one size fits all people” view of information literacy). The first two activities were used with a class of 80 taught postgraduate students; a class with students with a variety of first degree subjects and from many countries around the world (e.g. about a third of the class is Chinese). The first activity series made use both of a Virtual Learning Environment, WebCT, and face to face discussion. The presenter used 10 conceptions of information literacy discovered through research (Webber et al., 2005): each conception was set up as a thread on a WebCT discussion board and students were asked to choose (outside class time) the conception they identified with most, by posting to the relevant thread. The most “popular” conception turned out to be information literacy as “Becoming confident, autonomous learners and critical thinkers”. Students provided thoughtful comments, including some which referenced their own cultural/ national backgrounds. In a subsequent class, the “results” were discussed with the class, and students also discussed whether educators and information professionals needed to do anything differently to help people develop the student’s chosen conception of information literacy. − The second activity consisted of a seminar and a poster display. Students were set the task of producing posters that showed “What information literacy means to my future career”, with each group consisting of 3-6 students. In the first week the groups discussed the focus for their posters and drafted ideas. By the next week each group produced an A0 sized poster: these were put up in a display in Sheffield University’s Information Commons. The exhibition was attended by all students, and by Departmental staff and librarians. This was a very lively session, and the posters demonstrated the variety of career aspirations of the students (including library work in various sectors, but also management roles, consultancy, government posts etc.). Students were able to identify aspects of information literacy most important to them. The third activity involves a smaller number of students from the same cohort, using the Virtual World, Second Life. The presenter set up a three dimensional exhibition “What information/literacy means to me” based around quotations from the research study referred to above, and from another study by Shahd Salha (a PhD student researching Syrian school librarians’ conceptions of information literacy). People interact with the exhibition (as avatars), and are then encouraged provide their own quotations [this activity will take place in Spring 2010, but the exhibition is already in place]. In the subsequent roundtable the presenter would prefer to be led by the interests and questions of participants. However her own three questions would be: How have other participants exploited cultural/national differences in their students to gain a richer picture of information literacy? Have other participants used posters in their information literacy teaching? Have others used conceptions of information literacy derived from research in their teaching? References: Webber, S. Boon, S. and Johnston, B. (2005) “A comparison of UK academics' conceptions of information literacy in two disciplines: English and Marketing.” Library and Information Research, 30 (93), 4-15.